(untitled) (Philologia, 2021)
Foreign language and culture teaching and learning in Arab countries has acquired, as a pedagogical process, specificities which makes it today one of the main urgent concerns of research in educational sciences in this part of the world. Within a social context which is extremely permeated with cultural and ideological influences, many students tend to import social representations of the Other into the classroom, something which determines their readiness and learning strategies in their approach to foreign languages and cultures. This has induced among many Arab students of foreign languages and cultures a new type of motivation referred to in this paper as oppositional motivation. Oppositional motivation allows these students to distinguish between the foreign culture, towards which they have developed negative attitudes and representations, and its language they are psychologically disposed to learn, and thus overcome a psychological inhibition which would otherwise prevent them from learning the target language.